A Novel Molecular Method for Simultaneous Identification of Vibrio parahaemolyticus 57 K-Serogroups Using Probe Melting Curve Analysis - Lu, Linying; Li, Minxu; Li, Yinghui; Jiang, Min; Jiang, Yixiang; Shi, Xiaolu; Zuo, Le; Wang, Lei; Bian, Shengzhe; Qiu, Yaqun; Cai, Rui; Liao, Yiqun; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
The serotyping of V. parahaemolyticus, which is crucial to the surveillance and detection of outbreaks of vibriosis infection, has been widely used in many countries. In this study, we developed a molecular assay, named multiplex ligation reaction based on probe melting curve analysis (MLMA), for simultaneous identification of V. parahaemolyticus 57 K-serogroups. We conducted the whole genome sequencing analysis of 418 strains and analyzed 18 k-serogroup sequences from public databases and obtained 57 k-serogroup specific gene sequences for designing primers and probes. The developed MLMA assay for identifying the V. parahaemolyticus 57 K-serogroups showed high reproducibility, with intra- and inter-assay standard deviations and coefficients of variation of no more than 1°C and 1%, respectively. The limit of detection for all gene targets ranged from 0.1 to 1.0 ng/µL. We validated the MLMA assay with a double-blind test identifying 595 V. parahaemolyticus isolates using conventional serotyping methods for comparison. The results showed the kappa value between the MLMA assay and the traditional serological method was 0.936 and that there was a 96.97% consistency rate with conventional serotyping methods for all detected isolates. Additionally, five rare K-serogroups were identified using the MLMA assay, as well as 18 strains that could not be identified using the traditional serotyping method. Thus, the MLMA assay provides a rapid, robust, and promising tool for the molecular serotyping of V. parahaemolyticus K-serogroups and has the potential application to the detection of outbreaks and surveillance of V. parahaemolyticus infection.